A Fluorescent Chemosensor for Al3+ Based on CO Isomerization Derivated from Curcumin. Issue 7 (25th April 2016) - Li, Zhengyi; Yan, Jinbei; Yin, Yue; Zhang, Zhihui; Wang, Zhiming; Xu, Defeng; Sun, Xiaoqiang
Abstract: A simple and nontoxic fluorescent chemosensor of di‐ O ‐methyl curcumin has been prepared from curcumin. The sensor exhibited selective and sensitive fluorescent responses toward Al 3+ over a wide range of metal ions, such as Mn 2+, Ce 3+, Pt 2+, Sn 4+, Hg +, Sb 3+, K +, Ca 2+, Mg 2+, Ba 2+, Cu 2+, Ni 2+, Na +, NH4 +, Ag +, Pb 2+, Zn 2+, Fe 2+, Fe 3+, Hg 2+ and Cr 3+ in ethanol/water. The free ligand showed quite weak fluorescence emission due to the isomerization of CO double bond in the excited state, however, after addition of Al 3+, fluorescence emission results in a prominent fluorescence enhancement. Abstract : A simple and nontoxic fluorescent chemosensor based on CO isomerization derivated from curcumin has been prepared. The sensor exhibited selective and sensitive fluorescent responses toward Al 3+ over a wide range of metal ions in ethanol/water.